2019
DOI: 10.3390/ijms20081860
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenol-Rich Extract from Psiloxylon mauritianum, an Endemic Medicinal Plant from Reunion Island, Inhibits the Early Stages of Dengue and Zika Virus Infection

Abstract: The recent emergence and re-emergence of viral infections transmitted by vectors, such as the Zika virus (ZIKV) and Dengue virus (DENV), is a cause for international concern. These highly pathogenic arboviruses represent a serious health burden in tropical and subtropical areas of the world. Despite the high morbidity and mortality associated with these viral infections, antiviral therapies are missing. Medicinal plants have been widely used to treat various infectious diseases since millenaries. Several compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 49 publications
0
41
0
1
Order By: Relevance
“…In order to overcome these biofilm-producers alternative treatments include the use of antibiofilm agents produced by medicinal plants as this mode of action reduces the resistance susceptibility [11]. Plants, being an enriched source of naturally occurring biologically active components, play a vital role in the prevention and treatment of diseases by boosting immunity and reducing toxicity [12,13]. Ancient plants like W. coagulans contain many useful bioactive molecules such as withanolide, withaferin, withacoagin [14], etc., that have been used to synthesize therapeutic drugs for the prevention and treatment of various diseases due to their reduced side effects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these biofilm-producers alternative treatments include the use of antibiofilm agents produced by medicinal plants as this mode of action reduces the resistance susceptibility [11]. Plants, being an enriched source of naturally occurring biologically active components, play a vital role in the prevention and treatment of diseases by boosting immunity and reducing toxicity [12,13]. Ancient plants like W. coagulans contain many useful bioactive molecules such as withanolide, withaferin, withacoagin [14], etc., that have been used to synthesize therapeutic drugs for the prevention and treatment of various diseases due to their reduced side effects [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…An indigenous medicinal plant ubiquitous in the Reunion and Mauritius Islands, Psiloxylon mauritianum is widely used in traditional medicine among the local people for dysentery and common infectious diseases [113]. Given the high content of polyphenols present in P. mauritianum extract, a study evaluated its ability to inhibit ZIKV and DENV infections [113].…”
Section: Psiloxylon Mauritianum Extractmentioning
confidence: 99%
“…An indigenous medicinal plant ubiquitous in the Reunion and Mauritius Islands, Psiloxylon mauritianum is widely used in traditional medicine among the local people for dysentery and common infectious diseases [113]. Given the high content of polyphenols present in P. mauritianum extract, a study evaluated its ability to inhibit ZIKV and DENV infections [113]. The data showed that P. mauritianum extract was able to inhibit ZIKV attachment to the host cell surface, and was able to exert antiviral activity against four DENV serotypes [113].…”
Section: Psiloxylon Mauritianum Extractmentioning
confidence: 99%
See 2 more Smart Citations